Analysis of software engineering automation tools for Go (2021)
In this paper we discuss different software automation tools used for developing applications with the Go programming language. In this study we experimented with different kinds of tools, including code generating tools, static analysis tools, dynamic analysis tools, debuggers, formatters, and documentation generating tools. We focus on how these tools can be used to increase developer productivity while reducing possible bugs that could be solved at the development stage.